Enhanced chemical stability and sinterability of refined proton-conducting perovskite: Case study of BaCe0.5Zr0.3Y0.2O3−δ. Issue 6 (June 2015) - Hakim, Muhammad; Joo, Jong Hoon; Yoo, Chung-Yul; Kim, Byung-Kook; Yu, Ji Haeng
Abstract Improving the chemical stability and sinterability of proton-conducting perovskites has been a challenge for the development of durable electrochemical devices. In this study, we demonstrate that residual barium compounds after incomplete solid state reaction cause the chemical instability and poor sinterability of BaCe0.5Zr0.3Y0.2O3−δ (BCZY). As-calcined BCZY requires both a high sintering temperature (1470 °C) and controlled atmosphere (O2 purging) to obtain dense, crack-free ceramic specimens, but shows continuous degradation of electrical conductivity in the presence of trace amounts of CO2. The excess barium component, identified as mostly Ba(OH)2 by X-ray photoelectron spectroscopy, can be removed by rinsing the as-calcined powder with distilled water. Thermogravimetric analysis reveals that this refining process to remove Ba(OH)2 residues enhances the durability of BCZY in a CO2-containing atmosphere. From the refined BCZY, a dense, durable proton-conducting ceramic can be prepared by sintering at the relatively low temperature of 1360 °C.